Movimentos amplos na educação infantil: uma análise de experiências das crianças em uma UMEI no município de Santarém, Pará - SÁ, Erivelton Ferreira (Universidade Federal do Oeste do Pará, 2022)
This study aimed to analyze the experiences of large movements experienced by children in a preschool classroom in the city of Santarém, Pará. Specifically, we intend to analyze the municipal curricular proposal, the Pedagogical Proposal of the institution and the annual Planning of the teacher, verifying the experiences proposed with a focus on the broad movement of children; To characterize the routine of the institution, to perceive the moments in which the more ample movements are present; Understand the teacher's conception of broad movements and their role in child development; Understand the objectives of the broad-movement activities planned by the teacher. The theoretical basis for the development of the research was based on interactionist studies of human development, especially through the ideas of Wallon (1989), with the psychogenesis of child development, and the contributions of motor skills to the learning and development of the child; and Foucault (2014), which analyzes the mechanisms of education systems for the training of individuals' bodies. Based on the procedures developed the study is characterized as a qualitative research in education (BOGDAN; BIKLEN, 1994) and in field research (PRESTES, 2003). It occurred in a Municipal Infant Education Unit of the Municipality of Santarém, Pará, with a preschool class II, with fourteen children of five years old, and his teacher, graduated in full degree in Pedagogy. As a strategy for the construction of the data we make observations and filming of the activities developed with the children. A semistructured interview with the teacher was also carried out in two stages, the first consisting of questions about the academic and professional history of the teacher and his conception about the role of broad movements in child development; and the second, of the episodic type, from the teacher's perception about scenes from the class's daily life, which were captured during the observation period between August and October 2016. We used content analysis (BARDIN, 2011) to systematize and analyze the research data. We could verify that the pedagogical proposal and the annual planning of the teacher deal superficially with the pedagogical work with the broad movements of the children and, when predicting such issues, it is restricted to specific moments in the school calendar, such as the children's week and the day of folklore. We also verified that despite the institution's infrastructure and diverse environments, it would allow a variety of experiences of corporal expression and wide movements for children; these spaces are usually underutilized by the teacher, who most often develops his actions in the activity room or in the "maloca". As to the conceptions of child development, the teacher does not present theoretical basis to support them, but makes important reflections on the importance of broad movements for child development. The moments of the routine in which the broader movements are most present are those close to the exit time, when the teacher, evaluating that he has already achieved his goals with the "pedagogical activities", develops dance dance essays or leaves the children free to create its actions, while it is dedicated to the daily recording of occurrences and activities. The activities of wide movement observed emerged both on the initiative of the teacher and the children, the first being more valued by the teacher, which demonstrates an "adultcentric" vision. The teacher analyzes his actions, making important considerations and self-criticisms about his behaviors, evaluating his pedagogical work and thinking about new forms of action with the large movements of the children. In these terms, we consider that the children of the class studied already experience a multiplicity of experiences of wide movement, but that the intervention of the teacher could widen and diversify such experiences through an appropriate use of the spaces and materials, thus contributing to the better development child.